Remodeling of the heart in hypertrophy in animal models with myosin essential light chain mutations - Kazmierczak, Katarzyna; Yuan, Chen-Ching; Liang, Jingsheng; Huang, Wenrui; Rojas, Ana I.; Szczesna-Cordary, Danuta (Frontiers in Physiology, 2014)
Cardiac hypertrophy represents one of the most important cardiovascular problems yet the mechanisms responsible for hypertrophic remodeling of the heart are poorly understood. In this report we aimed to explore the molecular pathways leading to two different phenotypes of cardiac hypertrophy in transgenic mice carrying mutations in the human ventricular myosin essential light chain (ELC). Mutation-induced alterations in the heart structure and function were studied in two transgenic (Tg) mouse models carrying the A57G (alanine to glycine) substitution or lacking the N-terminal 43 amino acid residues (Δ43) from the ELC sequence. The first model represents an HCM disease as the A57G mutation was shown to cause malignant HCM outcomes in humans. The second mouse model is lacking the region of the ELC that was shown to be important for a direct interaction between the ELC and actin during muscle contraction. Our earlier studies demonstrated that >7 month old Tg-Δ43 mice developed substantial cardiac hypertrophy with no signs of histopathology or fibrosis. Tg mice did not show abnormal cardiac function compared to Tg-WT expressing the full length human ventricular ELC. Previously reported pathological morphology in Tg-A57G mice included extensive disorganization of myocytes and interstitial fibrosis with no abnormal increase in heart mass observed in >6 month-old animals. In this report we show that strenuous exercise can trigger hypertrophy and pathologic cardiac remodeling in Tg-A57G mice as early as 3 months of age. In contrast, no exercise-induced changes were noted for Tg-Δ43 hearts and the mice maintained a non-pathological cardiac phenotype. Based on our results, we suggest that exercise-elicited heart remodeling in Tg-A57G mice follows the pathological pathway leading to HCM, while it induces no abnormal response in Tg-Δ43 mice.